Engagement of TLR and Dectin-1/Syk Signaling Is Required for Activation of Notch Targets in Dendritic Cells. Issue 2 (9th June 2021) - Zhao, Yuna; Ju, Chanyang; Au, Karmen; Zhu, Jimmy; Zhao, Baohong; Shang, Yingli; Hu, Xiaoyu
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Pattern-recognition receptors, such as toll-like receptors (TLRs), detect a wide range of microbial products and initiate innate immune responses leading to the production of inflammatory mediators. In addition, TLR signaling also activates expression of Notch target genes that play crucial roles in suppression of TLR-triggered inflammatory responses. However, whether TLR signaling pathways engaged by other classes of pattern-recognition receptors induce expression of Notch target genes remains unclear. Here we demonstrate that zymosan, a stimulus for TLR2 and dectin-1, strongly induces expression of multiple Notch target genes in both human and murine dendritic cells. Mechanistically, induction of Notch targets by zymosan is both TLR2- and Syk-dependent through activation of mitogen-activated protein kinases and the transcription factor c-Fos. Hence, our data reveals a novel mechanism that efficient induction of Notch target genes requires engagement of TLR and dectin-1/Syk signaling pathways.